The Variations in the Level of Angiotensin II Between Subjects in Ajloun City and the Dead Sea Impact Hypertension Parameters - Al-Refaai, Taghreed A.; Al-Rawashdeh, Basel Naeem Fandy; Salem, Mai Abu; Blokh, Dyana; Mrayat, Reham; Al-Hamaideh, Ahlam Nasri Damen; Abeeleh, Jaafar Abu; Al-Shehabat, Mustafa Ahmad; Alkhatib, Ahed J.; abeeleh, Mahmoud abu (European Scientific Journal, ESJ, 2017)
Introduction: Jordan has a unique array of diversity among which having the deepest level in the world, the Dead Sea and an area with high attitudes in Ajloun City which gives us a great chance to study the biological effects on hypertension and possible impacts in selecting the appropriate treatment. Study objectives: to explore the impacts of variations of attitudes in hypertension and the level of beta blockers through studying the level of angiotensin II among study participants and to investigate if the patterns of anti-hypertensive treatments are impacted. Methods and subjects: a cross-sectional study design was carried out among participants from the two different areas. From each area, a total of 500 participants were recruited and surveyed through a questionnaire. Blood pressure was measured for all participants and blood samples were withdrawn to carry out the testing of angiotensin II. Data were analyzed statistically based on the appropriate software including excel and SPSS. The relationships were examined according to independent T-Test. Significance was considered according to p0.05). On the other hand, heart parameters including SBP, DBP, MBP, pulse, and PCV all of which were significantly higher in Ajloun than in the Dead Sea (p=0.001) for all selected variables. The level of angiotensin II was 12.08 Â± 5.19 pg/ml in Ajloun and this was higher than that of the Dead Sea (8.84 Â± 4.65 pg/ml). The difference in the mean of angiotensin II was statistically significant (p=0.039). Conclusion: the results of the present study showed that living in high altitude compared with the lowest area in the world (the Dead Sea) exposes persons for the risks of hypertension and other cardiovascular diseases. Our findings may lead to better therapeutic strategies particularly when to prescribe angiotensin II based therapies.